Hypertension Among Patients Presenting with Epistaxis in a Tertiary Care Center: A Descriptive Cross-sectional Study - Khakurel, Gita; Mahato, Nayan Bahadur (Nepalese Medical Journal, 2024)
Introduction: Epistaxis is one of the most common emergency conditions. Hypertension has been considered to be a major cause of spontaneous epistaxis for a long time. The objective of this study is to determine the prevalence of hypertension among patients presenting with epistaxis in a tertiary care hospital. Materials and Methods: A descriptive cross-sectional study was conducted in the patients visiting Kathmandu Medical College and Teaching Hospital with active nose bleeding from January 2023 to December 2023. Patients visiting the Emergency Department with active nose bleeding were included in the study by convenience sampling method. The blood pressure (BP)was measured in the Emergency Department at the time of presentation and patients with BP of >140/90 mmHg were considered to be hypertensive. Data was collected and statistical analysis was done in Statistical Packages for Social Services version 22. Results: A total of 250 patients were included in this study. The prevalence of hypertension in patients with epistaxis in the present study is 28.8 %. Hypertension was more common in males and elderly patients above 60 years. Conclusions: Our study showed that hypertension was more common in male and elderly patients Regular blood pressure monitoring should be advised for elderly patients. Other causes of epistaxis could be explored in future studies.